Development of a measure for the assessment of peer‐related positive emotional memories. (28th August 2017) - Ferreira, Cláudia; Cunha, Marina; Marta‐Simões, Joana; Duarte, Cristiana; Matos, Marcela; Pinto‐Gouveia, José
Abstract : Objectives: Previous research has demonstrated a link between early experiences of warmth, safeness, and soothing, and positive feelings, health, and well‐being outcomes. Although the impact of positive parent‐related early relationships and its posterior recall is well documented, research on the recall of warmth and safeness experiences within early peer relationships remains scarce. In fact, it is considered that the protective role of early positive peer relationships deserves intensive research; however, a specific measure that assesses this construct is still to be created. This study describes the development and validation of a new measure designed to assess the recall of early experiences of warmth, safeness, and affection in relation to peers (EMWSS‐peers). Design and methods: Distinct samples, comprising individuals of both genders aged between 18 and 68 years old, were used to test the EMWSS‐peers factorial structure through principal axis factoring (PAF) and confirmatory factor analysis (CFA), and to examine its psychometric properties. Results: Principal axis factoring's results indicated that the 12‐item scale presents a one‐factor structure explaining a total of 71.50% of the variance. The CFA confirmed the plausibility of this structure. The EMWSS‐peers also presented excellent internal consistency and construct, concurrent, and divergent validities. Conclusions: The EMWSS‐peers seems to be a new avenue for the study of memories of early experiences with friends and colleagues and may entail a relevant contribution to clinical and research fields, particularly for upcoming investigations on the relationship of peer‐related affiliative memories with well‐being and mental health. Practitioner points: The EMWSS‐peers is a specific measure to assess the recall of warmth and safeness in early peer relationships. The EMWSS‐peers is a brief, robust, and reliable self‐report instrument. The EMWSS‐peers presented excellent internal consistency and construct, concurrent, and divergent validities. The EMWSS‐peers may open a new avenue for the study of memories of early peer‐related experiences, with potential clinical and research implications.